Identification of Novel Polyphenolic Inhibitors of Shikimate Dehydrogenase (AroE). (August 2014) - Peek, James; Shi, Thomas; Christendat, Dinesh
Shikimate dehydrogenase (AroE) is an attractive target for herbicides and antimicrobial agents due to its conserved and essential nature in plants, fungi, and bacteria. Here, we have performed an in vitro screen using a collection of more than 5500 compounds and identified 24 novel inhibitors of AroE from Pseudomonas putida . The IC50 values for the two most potent inhibitors we identified, epigallocatechin gallate (EGCG) and epicatechin gallate (ECG), were 3.0 ± 0.2 µM and 3.7 ± 0.5 µM, respectively. Based on the high level of structural conservation between AroE orthologs, we predicted that the identified compounds would also inhibit AroE enzymes from other organisms. Consistent with this hypothesis, we found that EGCG and ECG inhibit the AroE domain of the bifunctional dehydroquinate dehydratase-shikimate dehydrogenase (DHQ-SDH) from Arabidopsis thaliana with IC50 values of 2.1 ± 0.3 µM and 2.0 ± 0.2 µM, respectively.